A kind of manufacturing process of anti-ultraviolet fabric

The combination of organic ultraviolet absorber formed by epoxidation treatment and grafting reaction with inorganic ultraviolet shielding agent and bonded with cotton fabrics in the form of chemical bonds, solving the problems of unsolid bonding of existing UV-resistant fabrics and poor washing resistance. It achieves efficient UV resistance and durability.

CN118932724BActive Publication Date: 2025-02-07FORMOSA TAFFETA (ZHONG SHAN) CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411005257.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-02-07
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The existing UV-resistant fabrics have poor bonding, insufficient durability and poor washing resistance, resulting in poor UV-resistant performance, especially after multiple washes, which significantly reduce the effect.

Method used

By epoxidizing the 2,4-dihydroxybenzophenone and reacting with amino-polyethylene glycol-aldehyde groups, the grafting of the organic ultraviolet absorber is achieved, and then dehydrated and condensed with the vapor-phase silica to form inorganic ultraviolet rays The composite of shielding agent is bonded to cotton fabrics in the form of chemical bonds to improve UV resistance.

Benefits of technology

The firmer bonding and durability of inorganic ultraviolet shielding agents is achieved, and the introduction of organic ultraviolet absorbers has significantly improved the UV resistance of cotton fabrics and can maintain excellent results after multiple washes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a manufacturing process of anti-ultraviolet fabric, and belongs to the field of textile technology. The present invention creatively utilizes epichlorohydrin to epoxidize 2,4-dihydroxybenzophenone, and then reacts with amino-polyethylene glycol-aldehyde group to realize the grafting of organic ultraviolet absorber, and finally dehydrates and condenses by adding fumed silica to realize the compounding of inorganic ultraviolet shielding agent, thereby preparing anti-ultraviolet filler, so that it can react with cotton fabric in an acidic environment after being dispersed in deionized water, realizes the bonding of chemical bonds, and thus gives cotton fabric excellent anti-ultraviolet effect, in practical application, on the one hand, inorganic ultraviolet shielding agent is not only more firmly combined, durable, and the introduction of organic ultraviolet absorber has a good promoting effect on the anti-ultraviolet performance of cotton fabric, on the other hand, cotton fabric still maintains excellent anti-ultraviolet ability after being washed many times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of textiles, and in particular relates to a manufacturing process of anti-ultraviolet fabrics. Background Art

[0002] Fabric is the material used to make clothing. As one of the three elements of clothing, fabric can not only interpret the style and characteristics of clothing, but also directly influence the color, shape and other performance effects of clothing. With many advantages such as warmth, heat resistance and hygiene, most of the fabrics currently used to make clothing are cotton fabrics, that is, cotton fabrics.

[0003] However, cotton fabrics often have weak anti-ultraviolet performance in actual applications, which seriously restricts their application scope. In order to meet people's increasingly high requirements for cotton fabrics, many existing technologies will add inorganic ultraviolet shielding agents to cotton fabrics to give cotton fabrics anti-ultraviolet performance. However, these existing technologies still have many disadvantages that limit their actual anti-ultraviolet effect. On the one hand, the combination is not firm and the durability is insufficient. The inorganic ultraviolet shielding agent is simply added to the cotton fabric in the form of physical blending, which is very easy to migrate and fall off the shielding agent. On the other hand, the water washability is poor. A large amount of friction during the washing process directly causes the shielding agent to be easily damaged and peeled off from the cotton fabric, which seriously affects the anti-ultraviolet performance.

[0004] Therefore, the current anti-ultraviolet fabrics still have many defects and are in urgent need of improvement. Summary of the invention

[0005] In view of the problems existing in the prior art, the purpose of the present invention is to provide a production process of anti-ultraviolet fabrics. The present invention creatively uses epichlorohydrin to perform epoxidation treatment on 2,4-dihydroxybenzophenone, and then reacts with amino-polyethylene glycol-aldehyde group to realize the grafting of organic ultraviolet absorber, and finally adds fumed silica for dehydration condensation to realize the compounding of inorganic ultraviolet shielding agent, so as to prepare anti-ultraviolet filler, which can react with cotton fabric in acidic environment after being dispersed in deionized water to realize chemical bond bonding, thereby giving cotton fabric excellent anti-ultraviolet effect. In practical application, on the one hand, the inorganic ultraviolet shielding agent is not only more firmly combined and durable, but also the introduction of organic ultraviolet absorber has a good promoting effect on the anti-ultraviolet performance of cotton fabric, and on the other hand, the cotton fabric still maintains excellent anti-ultraviolet ability after being washed many times.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A process for producing an anti-ultraviolet fabric, the process comprising the following steps:

[0008] (1) impregnating a cotton fabric with a sodium hydroxide solution at a weight ratio of 1:40-60 for 1-2 hours at a temperature of 80-90° C., filtering, then washing with deionized water until neutral, and vacuum drying at 50-60° C. to constant weight to obtain a cotton fabric A;

[0009] (2) adding an anti-ultraviolet filler dispersion to cotton fabric A, adjusting the pH to 3-4 with an acetic acid solution, and finally stirring the mixture at 60-80° C. for 3-5 hours to obtain a solution A;

[0010] (3) Filter solution A, remove the filtrate, then wash with deionized water until neutral, and vacuum dry at 50-60° C. until constant weight, and the preparation is completed.

[0011] As a preferred technical solution of the present invention, the cotton content of the cotton fabric in step (1) is 70-100%.

[0012] As a preferred technical solution of the present invention, the concentration of the sodium hydroxide solution in step (1) is 0.4-0.6 mol / L.

[0013] As a preferred technical solution of the present invention, the weight ratio of the cotton fabric A to the anti-ultraviolet filler dispersion in step (2) is 1:10-13.

[0014] As a preferred technical solution of the present invention, the anti-ultraviolet filler dispersion in step (2) is prepared by the following steps:

[0015] Step a: add 5-7 parts by weight of 2,4-dihydroxybenzophenone and 10-12 parts by weight of epichlorohydrin to 50-60 parts by weight of acetone, stir and mix at 75-90° C. for 5-10 minutes, then drip 30-35 parts by weight of sodium hydroxide solution while maintaining constant temperature and stirring, and continue to stir at constant temperature for 2-3 hours after the dripping is completed to obtain solution a;

[0016] Step b: Add ethyl acetate to solution a, stir for 10-15 minutes to mix, let stand for 1-2 hours to separate the layers, take the upper layer, and then distill at 50-60°C until the volatile liquid is completely removed to obtain product a;

[0017] Step c: adding 10-12 parts by weight of product a and 5-8 parts by weight of amino-polyethylene glycol-aldehyde to 60-80 parts by weight of toluene, stirring at 40-50° C. for 24-28 hours to react, then adding 7-8 parts by weight of fumed silica and 0.3-0.5 parts by weight of dibutyltin dilaurate, stirring at 70-80° C. for 5-7 hours to react, centrifuging, taking the precipitate, washing it with toluene 3-5 times, and finally vacuum drying at 70-80° C. until constant weight, to obtain product b;

[0018] Step d: Add 3-4 parts by weight of product b to 100 parts by weight of deionized water, stir for 20-30 minutes to complete the preparation.

[0019] Furthermore, the dripping speed in step a is controlled at 6-8 drops / s.

[0020] Furthermore, the mass concentration of the sodium hydroxide solution in step a is 4-5wt%.

[0021] Furthermore, the volume ratio of solution a to ethyl acetate in step b is 1:2-3.

[0022] Furthermore, the molecular weight of the amino-polyethylene glycol-aldehyde group in step c is 800-1000.

[0023] Furthermore, the specific surface area of ​​the fumed silica in step c is 100-150m 2 / g.

[0024] Furthermore, the centrifugal speed in step c is 3000-5000 r / min, and the centrifugal time is 8-10 min.

[0025] As a preferred technical solution of the present invention, the mass fraction of the acetic acid solution in step (2) is 8-10%.

[0026] Beneficial effects of the present invention:

[0027] (1) The present invention creatively utilizes epichlorohydrin to perform epoxidation treatment on 2,4-dihydroxybenzophenone, and then reacts with amino-polyethylene glycol-aldehyde group to achieve grafting of organic ultraviolet absorber, and finally adds fumed silica for dehydration condensation to achieve compounding of inorganic ultraviolet shielding agent, thereby preparing anti-ultraviolet filler, which can react with cotton fabric in acidic environment after being dispersed in deionized water to achieve chemical bond bonding, thereby giving cotton fabric excellent anti-ultraviolet effect. In practical application, on the one hand, the inorganic ultraviolet shielding agent is not only more firmly bonded and durable, but also the introduction of organic ultraviolet absorber has a good promoting effect on the anti-ultraviolet performance of cotton fabric, and on the other hand, cotton fabric still maintains excellent anti-ultraviolet ability after being washed many times.

[0028] (2) The present invention performs epoxidation treatment on 2,4-dihydroxybenzophenone organic UV absorber to make it have epoxy groups, then utilizes the epoxy groups to react with the amino groups in amino-polyethylene glycol-aldehyde groups to achieve the grafting of organic UV absorber, and finally utilizes the dehydration condensation of silanol and hydroxyl groups by adding fumed silica to achieve the compounding of inorganic UV shielding agent, thereby preparing anti-UV filler, creatively combining organic UV absorber and inorganic UV shielding agent together, and jointly exerting anti-UV performance, with better effect. At the same time, since there are aldehyde groups in the anti-UV filler, it can react with the hydroxyl groups of cotton fibers in cotton fabric in an acidic environment after being dispersed in deionized water, thereby bonding cotton fabric-organic UV absorber-inorganic UV shielding agent together in the form of chemical bonds, and in practical application, it gives cotton fabric excellent anti-UV durability.

[0029] (3) The anti-ultraviolet filler prepared by the present invention has a polyethylene glycol structure, that is, it contains a chain segment formed by multiple ether bonds. Therefore, in practical applications, its chain segment structure can be well coated on the surface of fumed silica and can form hydration when encountering water, thereby reducing the friction of fumed silica during washing, improving lubrication, and not easily damaging or peeling off cotton fabrics, thereby better exerting anti-ultraviolet performance. DETAILED DESCRIPTION

[0030] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0031] Example 1

[0032] A process for producing an anti-ultraviolet fabric, the process comprising the following steps:

[0033] (1) impregnating cotton fabric with sodium hydroxide solution at a weight ratio of 1:40 for 1 h at a temperature of 80° C., filtering, then washing with deionized water until neutral, and vacuum drying at 50° C. to constant weight to obtain cotton fabric A;

[0034] (2) adding the anti-ultraviolet filler dispersion to the cotton fabric A, adjusting the pH to 3 with an acetic acid solution, and finally stirring the mixture at 60° C. for 3 h to obtain a solution A;

[0035] (3) Solution A is filtered, the filtrate is removed, and then the solution is washed with deionized water until it becomes neutral, and then vacuum dried at 50° C. until it becomes constant weight. The preparation is completed.

[0036] The cotton content of the cotton fabric in step (1) is 100%.

[0037] The concentration of the sodium hydroxide solution in step (1) is 0.4 mol / L.

[0038] In step (2), the weight ratio of the cotton fabric A to the anti-ultraviolet filler dispersion is 1:10.

[0039] The anti-ultraviolet filler dispersion in step (2) is prepared by the following steps:

[0040] Step a: add 5 parts by weight of 2,4-dihydroxybenzophenone and 10 parts by weight of epichlorohydrin to 50 parts by weight of acetone, stir and mix at 75° C. for 5 minutes, then dropwise add 30 parts by weight of sodium hydroxide solution while maintaining a constant temperature and stirring, and continue to stir at a constant temperature for 2 hours after the dropwise addition is completed to obtain a solution a;

[0041] Step b: Add ethyl acetate to solution a, stir for 10 minutes, let stand for 1 hour to separate the layers, take the upper layer, and then distill at 50°C until the volatile liquid is completely removed to obtain product a;

[0042] Step c: adding 10 parts by weight of product a and 5 parts by weight of amino-polyethylene glycol-aldehyde to 60 parts by weight of toluene, stirring and reacting at 40° C. for 24 hours, then adding 7 parts by weight of fumed silica and 0.3 parts by weight of dibutyltin dilaurate, stirring and reacting at 70° C. for 5 hours, centrifuging, taking the precipitate, washing it with toluene for 3 times, and finally vacuum drying it at 70° C. until constant weight, to obtain product b;

[0043] Step d: Add 3 parts by weight of product b to 100 parts by weight of deionized water, stir for 20 minutes to complete the preparation.

[0044] The dripping speed of step a is controlled at 6 drops / s.

[0045] The mass concentration of the sodium hydroxide solution in step a is 4wt%.

[0046] The volume ratio of solution a and ethyl acetate in step b is 1:2.

[0047] The molecular weight of the amino-polyethylene glycol-aldehyde group in step c is 800.

[0048] The specific surface area of ​​the fumed silica in step c is 100 m 2 / g.

[0049] The centrifugal speed in step c is 3000 r / min and the centrifugal time is 8 min.

[0050] The mass fraction of the acetic acid solution in step (2) is 8%.

[0051] Example 2

[0052] A process for producing an anti-ultraviolet fabric, the process comprising the following steps:

[0053] (1) impregnating cotton fabric with sodium hydroxide solution at a weight ratio of 1:60 for 2 h at a temperature of 90° C., filtering, then washing with deionized water until neutral, and vacuum drying at 60° C. to constant weight to obtain cotton fabric A;

[0054] (2) adding an anti-ultraviolet filler dispersion to cotton fabric A, adjusting the pH to 4 with an acetic acid solution, and finally stirring the mixture at 80° C. for 5 h to obtain a solution A;

[0055] (3) Solution A is filtered, the filtrate is removed, and then the solution is washed with deionized water until it becomes neutral, and then vacuum dried at 60° C. until it becomes constant weight. The preparation is completed.

[0056] The cotton content of the cotton fabric in step (1) is 100%.

[0057] The concentration of the sodium hydroxide solution in step (1) is 0.6 mol / L.

[0058] In step (2), the weight ratio of the cotton fabric A to the anti-ultraviolet filler dispersion is 1:13.

[0059] The anti-ultraviolet filler dispersion in step (2) is prepared by the following steps:

[0060] Step a: add 7 parts by weight of 2,4-dihydroxybenzophenone and 12 parts by weight of epichlorohydrin to 60 parts by weight of acetone, stir and mix at 90° C. for 10 minutes, then drip 35 parts by weight of sodium hydroxide solution while maintaining constant temperature and stirring, and continue to stir at constant temperature for 3 hours after the dripping is completed to obtain solution a;

[0061] Step b: Add ethyl acetate to solution a, stir for 15 minutes, let stand for 2 hours to separate the layers, take the upper layer, and then distill at 60°C until the volatile liquid is completely removed to obtain product a;

[0062] Step c: adding 12 parts by weight of product a and 8 parts by weight of amino-polyethylene glycol-aldehyde to 80 parts by weight of toluene, stirring for 28 hours at 50° C., then adding 8 parts by weight of fumed silica and 0.5 parts by weight of dibutyltin dilaurate, stirring for 7 hours at 80° C., centrifuging, taking the precipitate, washing it with toluene 5 times, and finally vacuum drying at 80° C. until constant weight, to obtain product b;

[0063] Step d: Add 4 parts by weight of product b to 100 parts by weight of deionized water, and stir for 30 minutes to complete the preparation.

[0064] The dripping speed of step a is controlled at 8 drops / s.

[0065] The mass concentration of the sodium hydroxide solution in step a is 5wt%.

[0066] The volume ratio of solution a and ethyl acetate in step b is 1:3.

[0067] The molecular weight of the amino-polyethylene glycol-aldehyde group in step c is 1000.

[0068] The specific surface area of ​​the fumed silica in step c is 150 m 2 / g.

[0069] The centrifugal speed in step c is 5000 r / min and the centrifugal time is 10 min.

[0070] The mass fraction of the acetic acid solution in step (2) is 10%.

[0071] Example 3

[0072] A process for producing an anti-ultraviolet fabric, the process comprising the following steps:

[0073] (1) impregnating cotton fabric with sodium hydroxide solution at a weight ratio of 1:50 for 1.5 h at a temperature of 85° C., filtering, then washing with deionized water until neutral, and vacuum drying at 55° C. to constant weight to obtain cotton fabric A;

[0074] (2) adding the anti-ultraviolet filler dispersion to the cotton fabric A, adjusting the pH to 3.5 with an acetic acid solution, and finally stirring the mixture at 70° C. for 4 hours to obtain a solution A;

[0075] (3) Filter solution A, remove the filtrate, then wash with deionized water until neutral, and vacuum dry at 55° C. until constant weight, and the preparation is completed.

[0076] The cotton content of the cotton fabric in step (1) is 100%.

[0077] The concentration of the sodium hydroxide solution in step (1) is 0.5 mol / L.

[0078] In step (2), the weight ratio of the cotton fabric A to the anti-ultraviolet filler dispersion is 1:12.

[0079] The anti-ultraviolet filler dispersion in step (2) is prepared by the following steps:

[0080] Step a: add 6 parts by weight of 2,4-dihydroxybenzophenone and 11 parts by weight of epichlorohydrin to 55 parts by weight of acetone, stir and mix at 80° C. for 8 minutes, then dropwise add 33 parts by weight of sodium hydroxide solution while maintaining a constant temperature and stirring, and continue to stir at a constant temperature for 2.5 hours after the dropwise addition is completed to obtain a solution a;

[0081] Step b: Add ethyl acetate to solution a, stir for 13 minutes, let stand for 1.5 hours to separate the layers, take the upper layer, and then distill at 55°C until the volatile liquid is completely removed to obtain product a;

[0082] Step c: adding 11 parts by weight of product a and 7 parts by weight of amino-polyethylene glycol-aldehyde to 70 parts by weight of toluene, stirring for reaction at 45° C. for 26 hours, then adding 7.5 parts by weight of fumed silica and 0.4 parts by weight of dibutyltin dilaurate, stirring for reaction at 75° C. for 6 hours, centrifuging, taking the precipitate, washing it with toluene 4 times, and finally vacuum drying at 75° C. until constant weight, to obtain product b;

[0083] Step d: Add 3.5 parts by weight of product b to 100 parts by weight of deionized water, stir for 25 minutes to complete the preparation.

[0084] The dripping speed of step a is controlled at 7 drops / s.

[0085] The mass concentration of the sodium hydroxide solution in step a is 4.5wt%.

[0086] The volume ratio of solution a and ethyl acetate in step b is 1:2.5.

[0087] The molecular weight of the amino-polyethylene glycol-aldehyde group in step c is 900.

[0088] The specific surface area of ​​the fumed silica in step c is 120 m 2 / g.

[0089] The centrifugal speed in step c is 4000 r / min and the centrifugal time is 9 min.

[0090] The mass fraction of the acetic acid solution in step (2) is 9%.

[0091] Comparative Example 1

[0092] Based on Example 1, acetic acid solution was not added in step (2) to adjust the pH, and the rest remained unchanged.

[0093] Comparative Example 2

[0094] A process for producing an anti-ultraviolet fabric, the process comprising the following steps:

[0095] (1) impregnating cotton fabric with sodium hydroxide solution at a weight ratio of 1:40 for 1 h at a temperature of 80° C., filtering, then washing with deionized water until neutral, and vacuum drying at 50° C. to constant weight to obtain cotton fabric A;

[0096] (2) adding the anti-ultraviolet filler dispersion to the cotton fabric A, adjusting the pH to 3 with an acetic acid solution, and finally stirring the mixture at 60° C. for 3 h to obtain a solution A;

[0097] (3) Solution A is filtered, the filtrate is removed, and then the solution is washed with deionized water until it becomes neutral, and then vacuum dried at 50° C. until it becomes constant weight. The preparation is completed.

[0098] The cotton content of the cotton fabric in step (1) is 100%.

[0099] The concentration of the sodium hydroxide solution in step (1) is 0.4 mol / L.

[0100] In step (2), the weight ratio of the cotton fabric A to the anti-ultraviolet filler dispersion is 1:10.

[0101] The anti-ultraviolet filler dispersion in step (2) is prepared by the following steps:

[0102] Step a: add 5 parts by weight of 2,4-dihydroxybenzophenone and 10 parts by weight of epichlorohydrin to 50 parts by weight of acetone, stir and mix at 75° C. for 5 minutes, then dropwise add 30 parts by weight of sodium hydroxide solution while maintaining a constant temperature and stirring, and continue to stir at a constant temperature for 2 hours after the dropwise addition is completed to obtain a solution a;

[0103] Step b: Add ethyl acetate to solution a, stir for 10 minutes, let stand for 1 hour to separate the layers, take the upper layer, and then distill at 50°C until the volatile liquid is completely removed to obtain product a;

[0104] Step c: adding 10 parts by weight of product a and 5 parts by weight of amino-polyethylene glycol-aldehyde to 60 parts by weight of toluene, stirring at 40° C. for 24 hours to react, then distilling at 100° C. until the volatile liquid is completely removed to obtain a solid, washing it with carbon tetrachloride for 3 times, and finally vacuum drying at 70° C. until constant weight, to obtain product b;

[0105] Step d: Add 3 parts by weight of product b to 100 parts by weight of deionized water, stir for 20 minutes to complete the preparation.

[0106] The dripping speed of step a is controlled at 6 drops / s.

[0107] The mass concentration of the sodium hydroxide solution in step a is 4wt%.

[0108] The volume ratio of solution a and ethyl acetate in step b is 1:2.

[0109] The molecular weight of the amino-polyethylene glycol-aldehyde group in step c is 800.

[0110] The mass fraction of the acetic acid solution in step (2) is 8%.

[0111] Comparative Example 3

[0112] Based on Example 1, the molecular weight of the amino-polyethylene glycol-aldehyde group in step c was changed to 300, and the rest remained unchanged.

[0113] Test Example 1

[0114] UV protection performance test:

[0115] The anti-ultraviolet performance of the anti-ultraviolet fabrics prepared in Examples 1-3 and Comparative Examples 1-3 was tested according to the standard GB / T18830-2009.

[0116] Table 1. UV protection performance test results

[0117] UPF <![CDATA[T(UVA) AV ]]> Example 1 50+ <5% Example 2 50+ <5% Example 3 50+ <5% Comparative Example 1 50+ <5% Comparative Example 2 42 <5% Comparative Example 3 50+ <5%

[0118] Test Example 2

[0119] Washability test:

[0120] The anti-ultraviolet fabrics prepared in Examples 1-3 and Comparative Examples 1-3 were washed with deionized water and dried naturally, and this washing process was repeated 60 times. Then, the anti-ultraviolet performance test was performed according to the standard GB / T18830-2009.

[0121] Table 2. Washability test results

[0122] UPF <![CDATA[T(UVA) AV ]]> Example 1 50+ <5% Example 2 50+ <5% Example 3 50+ <5% Comparative Example 1 37 7.59 Comparative Example 2 39 6.96 Comparative Example 3 46 <5%

[0123] By comparing Examples 1-3, Comparative Examples 1-3 and Test Examples 1-2, it can be seen that:

[0124] The difference between Comparative Example 1 and Example 1 is that the anti-ultraviolet filler cannot form an effective chemical bond with the cotton fabric to combine.

[0125] The difference between Comparative Example 2 and Example 1 is that no fumed silica is added to the anti-ultraviolet filler.

[0126] The difference between Comparative Example 3 and Example 1 is that the molecular weight of the amino-polyethylene glycol-aldehyde group is reduced, that is, the number of ether bond structures is reduced.

[0127] It can be seen from Examples 1-3, Comparative Examples 1-3 and Test Example 1 that the manufacturing process of the present invention can obtain fabrics (cotton fabrics) with excellent UV protection performance.

[0128] It can be seen from Examples 1-3, Comparative Examples 1-3 and Test Example 2 that after multiple washings, the fabric (cotton fabric) obtained by the manufacturing process of the present invention still has excellent UV protection and good water resistance. At the same time, it can also be indirectly shown that the ether bond structure of amino-polyethylene glycol-aldehyde group can well protect the fumed silica during the washing process, preventing it from being damaged or peeled off from the cotton fabric due to friction.

[0129] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A process for producing anti-ultraviolet fabric, characterized in that: The manufacturing process comprises the following steps: (1) impregnating a cotton fabric with a sodium hydroxide solution at a weight ratio of 1:40-60 for 1-2 hours at a temperature of 80-90° C., filtering, then washing with deionized water until neutral, and vacuum drying at 50-60° C. to constant weight to obtain a cotton fabric A; (2) adding an anti-ultraviolet filler dispersion to cotton fabric A, adjusting the pH to 3-4 with an acetic acid solution, and finally stirring the mixture at 60-80° C. for 3-5 hours to obtain a solution A; (3) Filtering solution A, removing the filtrate, then washing with deionized water until neutral, and vacuum drying at 50-60° C. to constant weight, and the preparation is completed; The anti-ultraviolet filler dispersion in step (2) is prepared by the following steps: Step a: add 5-7 parts by weight of 2,4-dihydroxybenzophenone and 10-12 parts by weight of epichlorohydrin to 50-60 parts by weight of acetone, stir and mix at 75-90° C. for 5-10 minutes, then drip 30-35 parts by weight of sodium hydroxide solution while maintaining constant temperature and stirring, and continue to stir at constant temperature for 2-3 hours after the dripping is completed to obtain solution a; Step b: Add ethyl acetate to solution a, stir for 10-15 minutes to mix, let stand for 1-2 hours to separate the layers, take the upper layer, and then distill at 50-60°C until the volatile liquid is completely removed to obtain product a; Step c: adding 10-12 parts by weight of product a and 5-8 parts by weight of amino-polyethylene glycol-aldehyde to 60-80 parts by weight of toluene, stirring for 24-28 hours at 40-50° C., then adding 7-8 parts by weight of fumed silica and 0.3-0.5 parts by weight of dibutyltin dilaurate, stirring for 5-7 hours at 70-80° C., centrifuging, taking the precipitate, washing it with toluene 3-5 times, and finally vacuum drying at 70-80° C. until constant weight, to obtain product b; Step d: Add 3-4 parts by weight of product b to 100 parts by weight of deionized water, and stir for 20-30 minutes to complete the preparation; The molecular weight of the amino-polyethylene glycol-aldehyde group in step c is 800-1000.

2. The process for producing an anti-ultraviolet fabric according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in step (1) is 0.4-0.6 mol / L.

3. The process for producing an anti-ultraviolet fabric according to claim 1, characterized in that: In step (2), the weight ratio of the cotton fabric A to the anti-ultraviolet filler dispersion is 1:10-13.

4. The process for producing an anti-ultraviolet fabric according to claim 1, characterized in that: The mass concentration of the sodium hydroxide solution in step a is 4-5wt%.

5. The process for producing an anti-ultraviolet fabric according to claim 1, characterized in that: The volume ratio of solution a and ethyl acetate in step b is 1:2-3.

6. The process for producing an anti-ultraviolet fabric according to claim 1, characterized in that: The specific surface area of ​​the fumed silica in step c is 100-150m 2 / g.

7. The process for producing an anti-ultraviolet fabric according to claim 1, characterized in that: The centrifugal speed in step c is 3000-5000 r / min, and the centrifugal time is 8-10 min.

8. The process for producing an anti-ultraviolet fabric according to claim 1, characterized in that: The mass fraction of the acetic acid solution in step (2) is 8-10%.

Citation Information

Patent Citations

  • Preparation method of ultraviolet-proof cotton fabric

    CN110924160A